Advances in Peripheral Nerve Injury Repair with the Application of Nanomaterials. (21st May 2022) - Zhu, Jianqiang; Fu, Qingfeng; Song, Lujie; Liu, Leyi; Zheng, Zhiwen; Xu, Yong; Zhang, Zhihong
Abstract : Peripheral nerve injury (PNI) is a relatively common disease caused by various circumstances, ultimately affecting the life quality of patients. Although existing medications and surgical interventions have particular benefits for nerve repair, more effective therapeutic strategies are urgently needed for various types of nerve injuries. Increasing investigations of nanomaterials have demonstrated their excellent biological properties, such as biocompatibility, permeability, degradability, high medicine loading efficacy, suitable mechanical properties, and broad applications in the biomedical field. Concerning peripheral nerve (PN) repair, nanomaterials with outstanding biological properties can be fitted as nerve conduits to provide support and guidance for PN regeneration and loaded with functional cells, cytokines, or specific medications to promote regenerative outcomes further. Almost all existing studies have focused on the application of different nanomaterials in PN repair, while the application of nanomaterials in different PN injuries has not been taken into account. This article outlines the application of nanomaterials in the medical field and the prevalent therapeutic strategies for PN repair. Importantly, it focuses on the application of nanomaterials in various PNI diseases, covering injuries of the sciatic nerve, cavernous nerve, facial nerve, median nerve, and more.